Hydroxyl Assisted, Photoredox/Cobalt Co‐catalyzed Semi‐Hydrogenation and Tandem Cyclization of o‐Alkynylphenols for Access to 2, 3‐Dihydrobenzofurans. Issue 3 (14th December 2020) - Tian, Wan‐Fa; Zhu, Yao; He, Yong‐Qin; Wang, Mei; Song, Xian‐Rong; Bai, Jiang; Xiao, Qiang
Abstract: Herein, a hydroxyl assisted, photoredox/cobalt co‐catalyzed semi‐hydrogenation and tandem cyclization of o ‐alkynylphenols is developed towards direct assembly of 2, 3‐dihydrobenzofurans. Moderate to good yields were obtained for a range of sterically and electronically diverse 2‐propynolphenols under mild conditions. Mechanistic studies demonstrated the inevitable role of the alcoholic hydroxyl group with (Z)‐alkene as the real intermediate. Finally, a key low‐valent cobalt catalyzed intramolecular hydroetherification of alkene is proposed. Abstract :